Environmental Management and Higher Education: Are they Closely Related? - Dorothy Thompson; Nsikak-Abasi A. Etim; NseAbasi Etim (Newinera Publisher, 2020)
An empirical study was conducted to determine the relationship between higher education and environmental management. Through the multi-stage sampling procedure, the representative sample of 180 respondents were selected for the study. Primary data were obtained with the aid of questionnaire. Data were subjected to univariate probit regression analysis. Results revealed a positive relationship between environmental management and higher education. Findings showed that tertiary education was significant at one percent level suggesting that people who have acquired higher education were more likely to adopt and apply environmental management practices and techniques. Findings further revealed that the variable, no formal education, was negative and significant (P<0.05) indicating that persons without formal education were less likely to imbibe environmental management measures. Supportive policies and institutions which provide access to training and information (awareness and media sensitization) that will expand the opportunities of the poor to invest in environmental improvements are required. Policies to promote sound environmental management and protect the environmental assets through higher education would be a rational decision. The poor with low education must be seen first as part of the solution rather than part of the problem.